Electronic Participation Third IFIP WG 8.5 International Conference, ePart 2011, Delft, The Netherlands, August 29 – September 1, 2011. Proceedings - Tambouris, Efthimios.; Tambouris, Efthimios.; Macintosh, Ann.; Macintosh, Ann.; de Bruijn, Hans.; de Bruijn, Hans. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2011)
This book constitutes the refereed proceedings of the Third International Conference on Electronic Participation, ePart 2011, held in Delft, The Netherlands, in August/September 2011. The 26 revised full papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on appreciation of social media; visualizing arguments; understanding eParticipation; eParticipation initiatiaves and country studies; participation and eServices; and innovative technologies.